2016
DOI: 10.1182/blood-2015-07-660746
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic stimulation facilitates thrombopoiesis by promoting megakaryocyte adhesion, migration, and proplatelet formation

Abstract: Key Points NE and EPI promote megakaryocyte adhesion, migration, and proplatelet formation via α2-adrenoceptor-ERK1/2 signaling. Sympathetic stimulation enhances platelet production, which may facilitate recovery of thrombocytopenia or aggravate atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 48 publications
(66 reference statements)
4
43
0
Order By: Relevance
“…Therefore, the effect of MT3 receptor on MK activities needs to be further evaluated. The influence of MT during thrombopoiesis described in this study is consistent with our previous works in which we showed that some neuroendocrine hormones mainly affect the later stages of thrombopoiesis, where they induce a quick elevation of circulating platelets . This is different from some well‐known thrombopoietic cytokines such as TPO, IL‐3, and GM‐CSF, which mainly act during the early and middle stages of platelet production .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, the effect of MT3 receptor on MK activities needs to be further evaluated. The influence of MT during thrombopoiesis described in this study is consistent with our previous works in which we showed that some neuroendocrine hormones mainly affect the later stages of thrombopoiesis, where they induce a quick elevation of circulating platelets . This is different from some well‐known thrombopoietic cytokines such as TPO, IL‐3, and GM‐CSF, which mainly act during the early and middle stages of platelet production .…”
Section: Discussionsupporting
confidence: 91%
“…To detect human ploidy, cultured MKs were stained for CD41 + cells and then permeabilized with methanol and labeled with propidium iodide (PI, Invitrogen). CD41 + cells were gated for analysis, as previously described . Platelet production was investigated as reported, and pellets containing MKs and platelets were analyzed after labeling with CD41, CD42b, and PI (BioLegend or Emfret Analytics) after a two‐step centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…For example, studies under chronic stress showed that release of catecholamines from sympathetic nerves in the bone marrow affects megakaryopoiesis, leading to increased release of platelets into the circulation that are prone to activation in a α2‐AR‐ extracellular signal‐regulated kinase (ERK1/2)‐dependent manner. This enhanced thrombopoiesis of highly reactive platelets was shown to contribute to the aggravation of the atherosclerosis in ApoE‐deficient mice . In a somewhat similar way, sympatho‐adrenergic signalling triggered by a heart attack incites inhibitory effects on the distal bone marrow, through β3‐AR‐dependent adrenergic signalling in hematopoietic niche cells.…”
Section: Adrenergic Signalling During Vascular Inflammationmentioning
confidence: 88%
“…The adhesion assay was performed according to previous reports [17]. MKs derived from CD34 + cells were cultured for 11 days and pre-incubated with 2’,7’-bis-(2-carboxyethyl)-5-(-and-6)-carboxyfluorescein, acetoxymethyl ester (BCECF AM, Beyotime, China) for 1 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%